1995
DOI: 10.1007/bf00191799
|View full text |Cite
|
Sign up to set email alerts
|

A common ? hexosaminidase gene mutation in adult Sandhoff disease patients

Abstract: beta-Hexosaminidase gene mutations were analyzed in two adult-onset Sandhoff disease Italian patients by PCR analysis of a common known mutation (delta 5') and by heteroduplex analysis of genomic and RT-PCR DNA fragments, covering the whole gene. The patients' genotypes were delta 5'/C1214%, and G890A/C1214T, respectively. As mutation C1214T (Pro405Leu) is also present in the other two late-onset cases so far described, we suggest that C1214T is a common mutation in this type of Sandhoff disease. Mutation G890… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…However, using transfection experiments Wakamatsu et al showed that this variant actually causes the activation of a cryptic splice site which results in the loss of exon 11 from the processed transcript accounting for the loss of β-hexosaminidase activity [25]. Interestingly, this allele was observed once in each of the Finnish, Italian, and Japanese populations included in the 1000 Genomes sample which correlates well with the previous literature reports from Wakamatsu et al (Japanese patient) and Gomez-Lira et al (Italian patient) [25,28]. …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…However, using transfection experiments Wakamatsu et al showed that this variant actually causes the activation of a cryptic splice site which results in the loss of exon 11 from the processed transcript accounting for the loss of β-hexosaminidase activity [25]. Interestingly, this allele was observed once in each of the Finnish, Italian, and Japanese populations included in the 1000 Genomes sample which correlates well with the previous literature reports from Wakamatsu et al (Japanese patient) and Gomez-Lira et al (Italian patient) [25,28]. …”
Section: Resultssupporting
confidence: 86%
“…The c.1250C>T variant has been described by Wakamatsu et al and Gomez-Lira et al in compound heterozygous patients suffering from juvenile and adult onset Sandhoff disease respectively [25,28]. This variant results in the change of Pro at position 417 to Leu.…”
Section: Resultsmentioning
confidence: 99%
“…In G M2 gangliosidoses, the critical threshold of Hex A activity, inferred from the maximal activity of the respective enzyme in late-onset patients and the minimal activity of healthy probands, is $510% of the average activity (27). The P417L allele has been reported to be associated with a variety of late-onset phenotypes; a P417L mutation and a 16-kb deletion at the 5 0 -end were noted in a patient with the motor neuron disease phenotype (7). Both autonomic nervous system dysfunction and normal phenotype were observed in one family with the same combination of HEXB mutations (5).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a variety of less severe and chronic phenotypes of Sandhoff disease with a small percentage of residual Hex A activity have been reported, including motor neuron disease, spinocerebellar ataxia, intellectual disability and dysfunction of the autonomic nervous system (210). Only four missense mutations (Y456S, P504S, R533H and P417L) associated with the adult form of Sandhoff disease presenting the motor neuron disease phenotype have been reported (3,7,9,1113). In this study, we report the molecular and biochemical study of a Japanese male patient with the adult form of Sandhoff disease with the motor neuron disease phenotype.…”
mentioning
confidence: 99%
“…The initial history of the patient reported here has been previously described [10]. Briefly, he is a 53 year-old man who presented, at the age of 28, when he was a rock climber, with progressive difficulty in climbing and going down mountain paths and getting up from supine position.…”
Section: Case Reportmentioning
confidence: 99%